A Case of Transfusion Error in a Trauma Patient With Subsequent Root Cause Analysis Leading to Institutional Change. (3rd May 2016) - Clifford, Sean Patrick; Mick, Paul Brian; Derhake, Brian Matthew
A 28-year-old man presented emergently to the operating room following a gun-shot injury to his right groin. Our hospital's Massive Transfusion Protocol was initiated as the patient entered the operating room actively hemorrhaging and severely hypotensive. During the aggressive resuscitation efforts, the patient was inadvertently transfused 2 units of packed red blood cells intended for another patient due to a series of errors. Fortunately, the incorrect product was compatible, and the patient recovered from his near-fatal injuries. Root cause analysis was used to review the transfusion error and develop an action plan to help prevent future occurrences.